Endoscopic Ultrasound (EUS)-Guided Pancreatic Duct Drainage: The Basics of When and How to Perform EUS-Guided Pancreatic Duct Interventions - Christopher G. Chapman; Irving Waxman; Uzma D. Siddiqui (Korean Society of Gastrointestinal Endoscopy, 2016)
Despite the advances in endoscopy, endoscopic ultrasound-guided pancreatic duct drainage (EUS-PDD) remains a technically challenging procedure. Technical success rates are greater than 70%; however, the average rate of adverse events is nearly 20%, which increases to 55% when stent migration is included. Until recently, a significant difficulty with this technique was the absence of dedicated devices. Proper patient selection is of utmost importance, and EUS-PDD should be reserved for patients who have failed endoscopic retrograde pancreatography. Furthermore, EUS-PDD must be performed by experienced endoscopists who are familiar with the technique. The most common indications include chronic pancreatitis induced strictures and stones, disconnected pancreatic ducts, inaccessible ampulla, and post-surgical altered anatomy. This manuscript will review the accessories used, techniques employed, and published literature reporting outcomes as well as adverse events regarding EUS-PDD.